Pengaruh Kualitas Pelayanan Waiter/ Waitress Terhadap Peningkatan Kepuasan Konsumen Di Hotel Khas Parapat - Sintong Haleluya Simanungkalit; Ade Putera Arif Panjaitan; Rusmauli Simbolon; Maringan Sinambela; Harisan Boni Firmando (Jurnal Manajemen Pariwisata dan Perhotelan, 2023)
Service quality is a benchmark for service success determined by the level of satisfaction of service recipients. While the level of satisfaction of the recipient of this service will be obtained if a recipient of the service gets the type of service in accordance with what they expect and need. Thus, the needs of service recipients must be met as much as possible in order to obtain satisfaction. The data processing was obtained from questionnaire data collection data distributed to 50 respondents. Based on the results of the analysis and discussion described in the previous chapter, the author draws several conclusions on the results of the analysis that based on the hypothesis proposed by the researcher, a t test was carried out and obtained the SPSS output showed a calculated t value of 0.812 with a Sig of 0.421. To determine the level of significance of the research model, the calculated t value is compared with the table t value. Based on the results of the analysis, the hypothesis that states service quality (reliability, responsiveness, assurence, tangiable, emphaty) has a positive and significant effect on consumer satisfaction in the use of Parapat Khas Hotel services is empirically proven and acceptable.